4th weekend trade union course in Arnanlogh Community Centre. Behind the table fr.l.t.r.: (?), Stroud, Heath, Moore, Odhuno, Namfua, Belege and (?). Text on the back
4th weekend trade union course in Arnanlogh Community Centre. Behind the table fr.l.t.r.: (?), Stroud, Heath, Moore, Odhuno, Namfua, Belege and (?). Text on the back.